Helix Model in Gender-Based Tourism Development in Aceh Besar Regency, Aceh Province - Yuniningsih, Tri; Afrizal, Teuku; S, Mary Mangai; Hidayati, Rizki (PALASTREN: Jurnal Studi Gender, 2026)
Aceh Besar Regency boasts diverse tourism potential, yet women's roles in tourism governance remain limited. This study aims to analyze gender-based tourism development in Aceh Besar Regency and to examine the interaction and collaboration model among actors using the helix model. The main issue raised is the high level of women's participation in community-based tourism activities, which has not been matched by equal involvement in decision-making and destination governance. This study used a qualitative case study approach, drawing on in-depth interviews, field observations, and regional tourism policy documents. The results show that women play a dominant role in the tourism value chain, particularly in the culinary, homestay, and tourism MSME sectors, but still experience marginalization in institutional structures and strategic decision-making processes. The implementation of the pentahelix model in Aceh Besar involves the government, community, historians, business actors, and the media, but collaboration between actors tends to be hierarchical and procedural, with local government domination. The lack of integration of a gender perspective in collaborative governance results in women's empowerment being instrumental and not transformative. This study emphasizes the importance of institutionalizing a gender perspective within the pentahelix model to achieve inclusive and sustainable tourism.